Peningkatan Literasi Kalender Hijriah Global Tunggal dan Pelatihan Hisab Warga Muhammadiyah di PDM Kabupaten Pangakeje’ne Kepulauan Sulawesi Selatan - Alamsyah; S, Abdillah; Muthahharah, St; Algifari, Muh. Abu Dzar; Rahmania, Iffah; Jihan, Nur (Jurnal Pengabdian Kepada Masyarakat, 2025)
The Islamic calendar, which is based on the lunar cycle, plays a vital role in determining the timing of religious observances such as Ramadan, Eid al-Fitr, and Eid al-Adha. Differences in methods for determining the beginning of the lunar month often lead to a lack of synchronization among Muslims worldwide. Muhammadiyah offers a solution through the Unified Global Hijri Calendar (KHGT), which is unifying in nature and based on contemporary astronomical calculations (hisab hakiki). A community service program was carried out at the Muhammadiyah Regional Leadership (PDM) of Pangkep to enhance public literacy regarding the KHGT and improve the astronomical calculation skills of Muhammadiyah members. This was achieved through awareness campaigns, training sessions, and the distribution of pocketbooks. The results of the program showed a significant increase in participants' understanding of the KHGT concept. The KHGT not only addresses the need for a standardized Islamic calendar but also strengthens Islamic brotherhood (ukhuwah Islamiyah) and unity among the ummah. It is hoped that this training will produce human resources capable of disseminating KHGT knowledge at the branch and grassroots levels.